Research on the Development Approach for Reusable Model in Parallel Discrete Event Simulation - Jianbo Li; Yiping Yao; Wenjie Tang; Feng Zhu (Discrete Dynamics in Nature and Society)
Model reuse is an essential means to meet the demand of model development in complex simulation. An effective approach to realize the model reusability is to establish standard model specification including interface specification and representation specification. By standardizing model’s external interfaces, Reusable Component Model Framework (RCMF) achieves the model reusability acting as an interface specification. However, the RCMF model is presently developed just through manual programing. Besides implementing model’s business logic, modeler should also ensure the model strictly following the reusable framework, which is very distracting. And there lacks model description information for instructing model reuse or integration. To address these issues, we first explored an XML-based model description file which completed RCMF as the model representation and then proposed a RCMF model development tool—SuKit. Model description file describes a RCMF model and can be used for regenerating a model and instructing model integration. SuKit can generate a skeleton RCMF model together with a model-customized description file with the configured information. Modeler then just needs to concentrate on the model processing logic. The case study indicates that SuKit has good capability of developing RCMF models and the well-formed description file can be used for model reuse and integration.